Hydrogen monitoring requirements in the global technical regulation on hydrogen and fuel cell vehicles. (16th March 2017) - Buttner, W.; Rivkin, C.; Burgess, R.; Hartmann, K.; Bloomfield, I.; Bubar, M.; Post, M.; Boon-Brett, L.; Weidner, E.; Moretto, P.
Abstract: The United Nations Economic Commission for Europe Global Technical Regulation (GTR) Number 13 ( Global Technical Regulation on Hydrogen and Fuel Cell Vehicles ) is the defining document regulating safety requirements in hydrogen vehicles, and in particular, fuel cell electric vehicles (FCEVs). GTR Number 13 has been formally adopted and will serve as the basis for the national regulatory standards for FCEV safety in North America (led by the United States), Japan, Korea, and the European Union. The GTR defines safety requirements for these vehicles, including specifications on the allowable hydrogen levels in vehicle enclosures during in-use and post-crash conditions and on the allowable hydrogen emissions levels in vehicle exhaust during certain modes of normal operation. However, in order to be incorporated into national regulations, that is, to be legally binding, methods to verify compliance with the specific requirements must exist. In a collaborative program, the Sensor Laboratories at the National Renewable Energy Laboratory in the United States and the Joint Research Centre, Institute for Energy and Transport in the Netherlands have been evaluating and developing analytical methods that can be used to verify compliance with the hydrogen release requirements as specified in the GTR. Highlights: Three specific requirements within GTR – 13 were identified that regulate hydrogen levels within or around fuel cell electric vehicles. A thermoconductivity sensor can survive vehicle crash test and to verify compliance to the feul system integrity requirements for either H2 or He. A low-cost sensor-based measurement system is under development to verify compliance to tailpipe emissions requirements specified in the GTR.